Pengembangan Karier Guru Pada Keterampilan Karakter, Akademik, dan Motivasi Hasil Belajar Siswa - Amelia Risnauli br. Lumbangaol; Hamidah Hamidah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
Education in Indonesia now does not only emphasize students' academic grades. But it also emphasizes student skills, builds student character, and also increases learning motivation. This aims to ensure that education in Indonesia is not only based on numbers. Since ancient times, people have judged that smart students are students who get high grades. However, in the current era, education does not only look at high scores. Smart and outstanding students are considered to be able to apply the knowledge they gain while at school. So, students really understand how to apply the knowledge they gain in everyday life. That way, the knowledge he gets will be more useful.